(untitled) (Research, Society and Development, 2022)
Introduction: The use of active methodologies as a strategy for permanent health education at Hospital Federal da Lagoa. Objectives: The present work aims to present a study on the implementation of active methodologies for Nurses at the Federal Hospital of Lagoa and to collect their perceptions on the use of this type of methodology through a questionnaire. Methods: This is a qualitative and quantitative research, carried out between the months of october 2020 and february 2022, carried out through a questionnaire containing mixed questions (objective and essay). From the questionnaire, a construct of the collected information will be carried out, which will be the basis for the construction of the results and discussion. Results: There was a uniformity of opinions about the responses obtained in the questionnaire where they were positive about the implementation of active teaching methodologies in implemented training. Conclusion: During the research, it was possible to perceive that active methodologies are an excellent method of facilitating and interacting the teaching-learning process and interpersonal relationships, but despite many positive evidences about the use of active methodologies, as well as any innovation, it is still found, some difficulty in implementation, this fact is due to the use of active methodologies that require the rupture of paradigms. Therefore, in order to obtain success with the use of this type of methodology, commitment on the part of the institutions and professionals involved in this process is necessary.